Analysis of Total Antioxidant Capacity on Ingredients of Lotek Menu by Ferric Reducing Antioxidant Power Assay - Reni Banowati Istiningrum (EKSAKTA: Journal of Sciences and Data Analysis, 2013)
Total Antioxidant Capacity (TAC) determination has been made in the vegetable component of lotek with Ferric Reducing Antioxidant Power (FRAP) methods. Samples was crushed and then extracted with water as a polar solvent and centrifuged. The residue was extracted again with acetone as a non-polar solvent. The extract is then reacted with FRAP reagent and the absorbance measured by UV-Vis spectrophotometer at 595 nm. TAC values expressed as mM/mL extract of vegetables component of lotek for the water extract of green beans, peanuts, bean sprouts, cabbage, cucumbers, tomatoes, and spinach respectively is 2,72; 6,79; 1,26; 0,89; 0,33; 1,86; 1,85 mM /mL extract, while the acetone extract is 1,42; 5,41; 0,44; 0,32; 0,25; 1,09; 0,93 mM/mL extract. The three largest contribution to the total TAC is a water extract of peanuts, acetone extract of peanut and water extract of green beans respectively is 25,56; 21,16 and 10,66%.Keywords: lotek, TAC, FRAP, spectrophotometer UV-Vis